Analisis Retensi Rekam Medis Rawat Jalan Aktif ke Inaktif di UPT Puskesmas Sukarasa - Novi Indriyani Gunawan; Meita Nurseha; Meira Hidayati (Akademi Perekam dan Informasi Kesehatan Imelda, 2021)
Medical record retention is an activity of transferring medical record documents from an active storage room to an inactive storage room. Based on a preliminary survey at UPT Puskesmas Sukarasa, it is known that the puskesmas has retained outpatient medical record files 2 times in 2018 and 2019. But the retention is not done according to the SOP. The purpose of the study was to determine the implementation of outpatient medical record file retention at UPT Puskesmas Sukarasa. This type of research is descriptive with a retrospective approach. The research instrument was carried out by observation, interviews and checklist forms. The object of the research is the implementation of active to inactive outpatient medical record retention at UPT Puskesmas Sukarasa. The research subjects are the officer in charge of medical records and the person in charge of registration who performs retention of outpatient medical records.It is also known that the UPT Puskesmas Sukarasa already has an SOP on retention of medical records, but the SOP has not been implemented due to the lack of special staff for retention and the accumulation of medical record files on active storage shelves. Files that are retained are files for 2016-2018 without looking at the last date of treatment but based on the year number in the medical record file. Then the file is immediately moved to the inactive storage rack. It can be concluded that the implementation of retention at UPT Puskesmas Sukarasa is not in accordance with the SOP. It would be better if the retention is carried out according to the SOP with special and scheduled officers so that there is no accumulation of medical record files.